2019
DOI: 10.13005/bpj/1765
|View full text |Cite
|
Sign up to set email alerts
|

Antifungal Resistant in Non-Albicans Candida Species are Emerging as a Threat to Antenatal Women with Vulvovaginal Candidiasis

Abstract: Vulvovaginal candidiasis (VVC) is caused by Candida species. It has been associated with impact on economic cost. Currently, Non-albicans Candida species are more resistant to azoles and get converted from harmless to pathogenic state due to several virulence factors. Monitoring of the antifungal susceptibility pattern is important to know the resistant pattern of Candida species. Thus the objective of this research was to the identification of Candida in species level and to evaluate the antifungal resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Similar findings were reported in studies from India and Iran. 18,21 Our findings have shown that there is a need to change the content of the recommended Kit-2 in SCM of patients of vaginal discharge. We found voriconazole effective.…”
Section: Determination Of Minimum Inhibitory Concentration By E-test:...mentioning
confidence: 86%
See 1 more Smart Citation
“…Similar findings were reported in studies from India and Iran. 18,21 Our findings have shown that there is a need to change the content of the recommended Kit-2 in SCM of patients of vaginal discharge. We found voriconazole effective.…”
Section: Determination Of Minimum Inhibitory Concentration By E-test:...mentioning
confidence: 86%
“…17 Investigators from Tamil Nadu have reported 22% resistance to ketoconazole in C. albicans and 30% in C. krusei, whereas, all the isolates of Candida species showed 22.3% resistance to ketoconazole from Tamil Nadu. 18 The U.S. Food and Drug Administration (FDA) in its communication of July 2013 has limited the usages of ketoconazole oral tablets as they can cause severe liver injuries, adrenal gland problems and harmful drug interactions with other medications and therefore it should not be a first-line treatment for any fungal infection. However, the topical formulations of the drug have not been associated with such side effects.…”
Section: Determination Of Minimum Inhibitory Concentration By E-test:...mentioning
confidence: 99%
“…The modified Kirby-Bauer disc diffusion method was used to test antifungal susceptibility. Mueller-Hinton Agar with 2% Glucose and 0.5 g/mL Methylene Blue Dye (GMB) Medium agar culture plate was uniformly seeded with the organism to be tested in this method [ 17 , 18 ]. All of the Candida species tested against commercially available antimicrobial disks (purchased and imported from Liofilchem, Italy) were used in this study.…”
Section: Methodsmentioning
confidence: 99%